Investigating socioecological obesogenic factors in children with Autism Spectrum Disorder - TaeEung Kim; Eun Hye Kwon (Frontiers Media S.A., 2022)
Obesity-related information in children with Autism Spectrum Disorder (ASD) is limited, and research findings are contradictory. Thus, this study aimed to use a nationwide non-clinical sample to examine the association of sociological factors with overweight status in children with ASD and reveal the degree of differences in the risk factors for overweight in children with and without ASD. The data for this cross-sectional study, based on the modified ecological system theory model, were obtained from the 2019 National Survey of Children's Health. The weighted logistic regressions were performed to determine the factors associated with overweight status in children with ASD, controlling for demographics, physical activity-related behaviors, and family and environmental conditions. A total of 529 children were identified (mean age 13.78 years, 83.21% boys). Two-parent households, less healthy parents and households, households with smokers, poor sleep quality, and greater participation in organized activities were associated with a higher likelihood of overweight in children with ASD (all P < 0.05). The determinants of obesity among children with ASD go beyond the individual level; family and community support are important. Therefore, greater attention should be directed toward the families of children with ASD and community-level administrative policies to improve quality of life by preventing or reducing obesity in children with ASD.